2013
DOI: 10.1111/pcn.12075
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome in stroke survivors after discharge from a convalescent rehabilitation ward

Abstract: Aim:The aim of this study was to investigate the long-term mortality, daily living activities, social activity, and symptoms of depression, in post-stroke patients discharged to their homes from a convalescent rehabilitation ward, and to determine the relationship between demographic variables and long-term outcome.Methods: This study included 252 consecutive stroke patients (140 men; mean age, 72.4 ± 10.8 years) who had been admitted to a convalescent rehabilitation ward for inpatient rehabilitation. Follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…In our previous cross‐sectional studies, we have shown that social inactivity and depression symptoms remain highly prevalent in home‐dwelling stroke survivors after discharge from a convalescent rehabilitation ward . Maintaining and improving ADL acquired through inpatient rehabilitation is important for stroke survivors to be able to continue living at home.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous cross‐sectional studies, we have shown that social inactivity and depression symptoms remain highly prevalent in home‐dwelling stroke survivors after discharge from a convalescent rehabilitation ward . Maintaining and improving ADL acquired through inpatient rehabilitation is important for stroke survivors to be able to continue living at home.…”
Section: Introductionmentioning
confidence: 98%
“…Post-stroke depression (PSD) is one of the most common mental complications suffered by stroke patients leading to an impaired quality of life (QoL), altered rehabilitation outcomes, and an increased mortality rate 12345. At 3 months after a stroke, the independent predictors for PSD include a low level of education, low income, a greater severity of stroke, being younger than 68 years of age, the presence of a severe functional disability, crying behaviors, self-reported problems with activities of daily living (ADL), and the need for help during ADL 67…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of stroke survivors report persistent hemiparesis resulting in impaired fine and gross motor skills of the upper extremity (5), (6). Various studies have shown that early care, high intensity and functional involvement of the movements practiced is directly proportional to a better recovery (7), (8).…”
Section: Constrained Induced Movement Therapy (Cimt)mentioning
confidence: 99%
“…Studies have shown that more than 60% of stroke survivors report persistent hemiparesis resulting in impaired fine and gross motor skills of the upper extremity (40), (5), (6). Manual dexterity involving handling and manipulating objects with the fingers and hand is important for nearly all daily life activities such as dressing, grooming, eating, etc.…”
Section: Introductionmentioning
confidence: 99%